2011
DOI: 10.1002/anie.201103028
|View full text |Cite
|
Sign up to set email alerts
|

Selective Endo and Exo Binding of Alkali Metals to Corannulene

Abstract: The ion size matters: the structures of corannulene monoanions crystallized with Cs(+) and Rb(+) ions in the presence of [18]crown-6 reveal the intrinsic binding preferences of alkali metals and allow evaluation of the bowl deformation caused by negative charge distribution and metal binding. The large cesium cation coordinates exclusively to the concave face of C(20) H(10)(-), whereas the smaller rubidium cation exhibits convex binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 56 publications
(49 reference statements)
17
65
0
Order By: Relevance
“…Noncovalent functionalization of buckybowls (S and R) and contrasting their pattern with the planar coronene provides us important insights into the binding mechanism and the preferential binding surfaces and sites. The regio and stereo selectivity of metal ion binding to buckybowls is interesting in its own right, and this has been extensively studied . The structural, energetic and functional properties of buckybowls and their interaction with the models of π systems has also been reported …”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent functionalization of buckybowls (S and R) and contrasting their pattern with the planar coronene provides us important insights into the binding mechanism and the preferential binding surfaces and sites. The regio and stereo selectivity of metal ion binding to buckybowls is interesting in its own right, and this has been extensively studied . The structural, energetic and functional properties of buckybowls and their interaction with the models of π systems has also been reported …”
Section: Introductionmentioning
confidence: 99%
“…[24,25] The other smallest bowl that can be mapped onto C 60 is sumanene C 21 H 12 , quite recently synthesized and which corresponds to a bowl with a six-carbon ring at the bottom. [24,[39][40][41]44,45,[47][48][49]51] However, in a previous work by our group, it has been shown that corannulene substituted with electron-withdrawing groups is able to form stable complexes with anions. [45,51] To the best of our knowledge, most studies in literature deal with the interaction of cations and these unsubstituted bowls.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Indeed, the controlled reduction of C 28 H 14 in diglyme using 1.2 equiv of cesium metal affords an intense green solution in 12 hours,which upon slow diffusion of hexanes at 10 8 8Cp roduces single crystals of 1 suitable for the X-ray diffraction studies (See the Supporting Information for more details). [17] Indeed, the controlled reduction of C 28 H 14 in diglyme using 1.2 equiv of cesium metal affords an intense green solution in 12 hours,which upon slow diffusion of hexanes at 10 8 8Cp roduces single crystals of 1 suitable for the X-ray diffraction studies (See the Supporting Information for more details).…”
mentioning
confidence: 99%